The IntI1 Integron Integrase Preferentially Binds Single-Stranded DNA of the attC Site - Francia, M. Victoria (American Society for Microbiology, 1999)
IntI1 integrase is a member of the prokaryotic DNA integrase superfamily. It is responsible for mobility of antibiotic resistance cassettes found in integrons. IntI1 protein, as well as IntI1-COOH, a truncated form containing its carboxy-terminal domain, has been purified. Electrophoretic mobility shift assays were carried out to study the ability of IntI1 to bind the integrase primary target sites attI and aadA1 attC. When using double-stranded DNA as a substrate, we observed IntI1 binding to attI but not to attC. IntI1-COOH did not bind either attI or attC, indicating that the N-terminal domain of IntI1 was required for binding to double-stranded attI. On the other hand, when we used single-stranded (ss) DNA substrates, IntI1 bound strongly and specifically to ss attC DNA. Binding was strand specific, since only the bottom DNA strand was bound. Protein IntI1-COOH bound ss attC as well as did the complete integrase, indicating that the ability of the protein to bind ss aadA1 attC was contained in the region between amino acids 109 and 337 of IntI1. Binding to ss attI DNA by the integrase, but not by IntI1-COOH, was also observed and was specific for the attI bottom strand, indicating similar capabilities of IntI1 for binding attI DNA in either double-stranded or ss conformation. Footprinting analysis showed that IntI1 protected at least 40 bases of aadA1 attC against DNase I attack. The protected sequence contained two of the four previously proposed IntI1 DNA binding sites, including the crossover site. Preferential ssDNA binding can be a significant activity of IntI1 integrase, which suggests the utilization of extruded cruciforms in the reaction mechanisms leading to cassette excision and integration.